Hydrothermal synthesis of 3D disulfide nanoparticles molybdenum / carbon - Shyiko, L.O.; Budzulyak, I.M.; Ravsky, M.; Kulyk, Yu.O.; Kotsyubinsky, V.O. (Physics and Chemistry of Solid State, 2015)
The results of the synthesis of 3D multilayer nanoparticles of molybdenum disulfide / carbon by hydrothermal synthesis with the use of cetyltrimethylammonium cation as micelles are presented in the paper. The elemental composition, structural and morphological properties of the obtained materials were investigated by X-ray diffractometry, transmission electron microscopy, energy-dispersive X-ray spectrometry and adsorption porometry. The synthesized nanoparticles, preferably spherical in shape with an average size of 40-70 nm, have been found to have a doublet-hierarchical structure in which 2H-MoS2 layers alternate with carbon layers (atomic ratio of about 1: 1). Annealing at a temperature of 500 ° C in an argon atmosphere leads to the destruction of nanospheres, but does not change the atomic Mo: S ratio.